Pengaruh Perawatan Luka terhadap Penyembuhan Luka Heating Perineum Ibu di PMB yang ada di Wilayah Kerja Puskesmas Teupin Raya Kecamatan Glumpang Tiga Kabupaten Pidie - Zaitun Zaitun; Salamah Salamah (KOLONI, 2023)
Postpartum mothers generally don't really understand how to treat perineal wounds, mothers think it's normal and can heal on its own, especially in mothers who have given birth more than once. Mother's knowledge about Personal Hygiene is an indicator in the process of accelerating perineal wound healing. Personal hygiene that is not carried out properly can be at risk of causing postpartum infections due to wounds in the perineum, lacerations in the genital tract including the perineum, vaginal walls and cervix so that it will affect the length of wound healing. Based on World Health Organization (WHO) data in 2017, around 830 women die every day due to complications during pregnancy or childbirth. To reduce the risk of maternal death globally from 216,100,000 live births in 2015 to 70 per 100,000 live births in 2030. The aim of this research is to determine the effect of wound care on the healing of perennial heating wounds in the Teupin Raya Community Health Center working area in 2023. Design This research uses an observation method with a cross-sectional approach. The population in this study was all postpartum mothers (0-40 days). The sampling technique uses Total Population. The research results were obtained from 30 respondents, namely poor wound care and slow wound healing as many as 2 respondents (6.7%), adequate wound care with normal wound healing as many as 1 respondent (3.3%) good wound care with fast wound healing as many as 9 respondents ( 30.0%) and normal wound healing was 18 respondents (60.0%). The Chi-square test results show that with p-value = 0.000. It is recommended that postpartum mothers improve wound care by cleaning the genital area every day. Keywords: Treatment, healing of maternal perineal wounds